Prevalence and correlates of alcohol use among adolescents attending school in Kerala, India. (29th December 2015) - Jaisoorya, T.S.; Beena, K.V.; Beena, M.; Ellangovan, K.; Jose, Dalia C.; Thennarasu, K.; Benegal, Vivek
Abstract: Introduction and Aims: Concern around potentially increasing alcohol use among young people has been growing in public discourse in India. However, there are few published studies on this issue. We studied the prevalence, patterns and correlates of alcohol use among adolescents in Ernakulam, Kerala State, India. Design and Methods: A total of 7560 students in the age group 12–19 years from 73 schools completed a self‐administered questionnaire incorporating standardised instruments to assess alcohol use. Results: The overall prevalence of lifetime alcohol among adolescents use was 15% (23.2% among boys and 6.5% among girls) with prevalence increasing with age, and 25.3% of drinkers reported hazardous alcohol use. The mean age at onset of alcohol use was 13.6 years. Initiation of alcohol use typically preceded use of tobacco and illicit drugs. Most students reported initiation into alcohol use by family members in the context of family celebrations. The prevalence of alcohol use was higher among students from urban areas and those with a part‐time job. Lower use was seen among Muslims. Lifetime alcohol use was associated with significantly higher tobacco and illicit drug use, suicidal thoughts, attention deficit hyperactivity disorder symptom‐scores, history of non‐contact sexual abuse and with poor academic performance. Discussion and Conclusions: Alcohol use among adolescents in India deserves greater attention than it has previously received, marked as it is by an early onset and associated with a range of negative mental health problems. [ Jaisoorya T S, Beena K V, Beena M, Ellangovan K, Jose D C, Thennarasu K, Benegal V. Prevalence and correlates of alcohol use among adolescents attending school in Kerala, India. Drug Alcohol Rev 2016;35:523–529]